Strategi Kepala Madrasah Untuk Memperkuat Karakter Kreatif Siswa di MTs Baiturrahim Kabar - Muhammad Fahrurrozi; Ita Raodatul Fahmi; Nurul Yakin; Asriati Aulia Malik (Lembaga Einstein College (LEC), 2024)
This research aims to 1) determine the Madrasah Head's efforts in strengthening the creative character of students at MTs Baiturrahim Kabar and 2) the supporting and inhibiting factors. This research uses a descriptive-qualitative approach. Data was obtained through observation, interviews, and documentation techniques. The data analysis technique uses Miles and Huberman's theory, which includes data condensation, data presentation, and drawing conclusions. Based on the results of research in the field, it was found that 1) the efforts of the Madrasah Head to strengthen the creative character of students at MTs Baiturrahim Kabar, namely, firstly initiating sewing extracurricular activities, secondly an appeal to hold a live pharmacy, thirdly implementing typical Lombok cooking skills as a use of craft class hours, and fourthly the development of language skills through English and Arabic extracurricular activities. 2) Supporting factors, namely optimism as the spirit of activity, achievement motivation, support from the community, and adequate facilities. The inhibiting factors are health conditions that are sometimes less stable, the depletion of the Madrasah Head's energy and thoughts due to a lack of educational staff, the presence of some of the student parents' responsibility for funding, and complaints from a small number of teachers about the Madrasah Head's policies